The quality, suitability, content and readability of online health‐related information regarding sexual dysfunction after rectal cancer surgery. (28th January 2021) - Brissette, Vincent; Alnaki, Ali; Garfinkle, Richard; Lloyd, Marshall; Demian, Marie; Vasilevsky, Carol‐Ann; Morin, Nancy; Boutros, Marylise
Abstract: Aim: Patients are not well informed about sexual dysfunction after rectal cancer surgery and often turn to the Internet for information. The purpose of this study was to assess online information for patients on sexual dysfunction after rectal cancer surgery. Methods: An online search of Google, Yahoo and Bing was performed using specific (e.g., rectal cancer surgery and vaginal pain) and general (e.g., rectal cancer surgery and sex) search terms. Inclusion criteria were websites in English, designed for patients, and including content regarding sexual dysfunction after rectal cancer surgery. Websites were assessed for readability (nine standardized tests), quality (DISCERN tool), suitability (Suitability Assessment of Materials tool), and content. Results: Of 5040 websites identified, 99 unique websites met inclusion criteria. Three (3%) websites fulfilled the American Medical Association recommendation of a 6th‐grade reading level. Using the DISCERN instrument, two (2%) websites were assigned good/excellent quality, nineteen (19%) referenced their sources of information, and thirty‐one (31%) fully discussed the impact of sexual dysfunction on quality of life. Using the SAM instrument, three (3%) websites were classified as highly suitable for rectal cancer patients, sixty‐five (66%) were adequate, and thirty‐one (31%) were inadequate. With regards to content, nine (9%) websites fully discussed the impact of sexual dysfunction on patients partners and fifty‐one (52%) websites did not cover prognosis. Conclusion: Online health information available to patients on sexual dysfunction after rectal cancer surgery is suboptimal. Websites are not suitable, lack important content, and are written at too complex a reading level for patients.